PENGARUH PERCEIVED EASE OF USE, PERCEIVED USEFULNESS DAN TRUST TERHADAP REPURCHASE INTENTION - Saraswati, I Gusti Agung Ayu Permata; Rahyuda, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.02.TAHUN. 2021, 2021)
Repurchase intention is the behavior of consumers to repurchase products or services from the same company based on their previous purchase experience. The factors that influence the occurrence of repurchase intention include perceived ease of use, perceived usefulness, and trust. The purpose of this study was to determine the influence of these factors on Shopee users in Denpasar City. The study used a sample size of 140 Shopee user respondents in the city of Denpasar, with a non-probability sampling method, particularly purposive sampling. Collecting questionnaire data using Google Forms to respondents. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that (1) perceived ease of use has a positive and significant effect on repurchase intention (2) perceived usefulness  has a significant positive effect on repurchase intention (3). trust has a significant positive effect on repurchase intention. Based on this, it can be concluded that perceived ease.of use, perceived.usefulness , and good trust greatly affect the repurchase.intention behavior of Shopee users in Denpasar City. Shopee management should pay attention to perceived ease.of use, perceived.usefulness, and trust in order to maintain repurchase.intention behavior.